2011
DOI: 10.1093/sleep/34.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Neurons of the Sublaterodorsal Tegmental Nucleus Triggering Paradoxical (REM) Sleep Are Glutamatergic

Abstract: This finding adds further evidence to the concept that PS-on neurons of the SLD generating PS are of small size and glutamatergic in nature. By means of their descending projections to medullary and/or spinal glycinergic/GABAergic premotoneurons, they may be especially important for the induction of muscle atonia during PS, a disturbed phenomenon in narcolepsy and REM sleep behavior disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 16 publications
5
96
2
1
Order By: Relevance
“…Then, Lu et al [63] reported for the first time the presence of vGlut2-containing neurons in the SLD. We recently further demonstrated that most of the Fos-labeled neurons localized in the SLD after PS recovery express vGlut2 [21]. Altogether, these results indicate that the PS-on SLD neurons triggering PS are glutamatergic.…”
Section: Sld Neurons Triggering Ps Are Glutamatergicmentioning
confidence: 63%
“…Then, Lu et al [63] reported for the first time the presence of vGlut2-containing neurons in the SLD. We recently further demonstrated that most of the Fos-labeled neurons localized in the SLD after PS recovery express vGlut2 [21]. Altogether, these results indicate that the PS-on SLD neurons triggering PS are glutamatergic.…”
Section: Sld Neurons Triggering Ps Are Glutamatergicmentioning
confidence: 63%
“…In contrast, functional mapping studies using the c-fos method in animals with a compensatory hyper-expression of REMS after sustained periods of REMS deprivation did not report any significant activation of the medial parabrachial nucleus (Verret et al, 2005;Clément et al, 2011). These studies identified clusters of activated neurons in the central subnucleus of the lateral parabrachial complex (Verret et al, 2005;Clément et al, 2011).…”
Section: The Role Of the Parabrachial Complex In Remsmentioning
confidence: 68%
“…These studies identified clusters of activated neurons in the central subnucleus of the lateral parabrachial complex (Verret et al, 2005;Clément et al, 2011).…”
Section: The Role Of the Parabrachial Complex In Remsmentioning
confidence: 99%
“…The VLPO sends inhibitory projections to the areas of the pontine tegmentum (as well as the ventrolateral periaqueductal gray area) not active during REM, thus "REM-off" neurons. These neurons then project to other "REM-on" areas of the brain, including glutamatergic neurons that send inhibitory messages to the spine, contributing to the muscle atonia associated with REM sleep (Clement, Sapin, Berod, Fort, & Luppi, 2011;Fuller & Lu, 2009;. In fact, recent evidence suggests that damage to the glutamatergic regions projecting to the spine may have some involvement in REM behavior disorder, a sleep dysfunction that exhibits signs of REM sleep without muscle atonia, as well as the cataplexy associated with the most well-known REM disorder, narcolepsy Luppi et al, 2011).…”
Section: Rem Sleepmentioning
confidence: 99%